Bellman functions and dimension free Lp-estimates for the Riesz transforms in Bessel settings. (August 2020) - Betancor, Jorge J.; Dalmasso, Estefanía; Fariña, Juan C.; Scotto, Roberto
Abstract: In this article we prove dimension free L p –boundedness of Riesz transforms associated with a Bessel differential operator. We obtain explicit estimates of the L p –norms for the Bessel–Riesz transforms in terms of p, establishing a linear behavior with respect to p . We use the Bellman function technique to prove a bilinear dimension free inequality involving Poisson semigroups defined through this Bessel operator.